STRATEGI CUSTOMER RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN - Sri Setyo Iriani (Jurnal Keuangan dan Perbankan, 2011)
Competition in the banking industry had rapidly gave freedom to our customers in determining the choice touse their services, so if the value received was not as expected, then the customers were easy to move to anotherbank, which was considered in accordance with their wishes. Thus, banks were implementing various strategies,both offensive and defensive oriented. Defensive strategy was oriented to maintain customers by buildingrelationships with customers so that customers will be loyal to the bank. This study aimed to examine the effectof customer relationship marketing strategy on customer loyalty of BNI and BCA in East Java. Total samplewas 210 clients, 105 clients each of BNI and BCA. Data was collected using interviews and questionnaires. Theresults showed that there was influence of customer relationship marketing strategy on customer loyalty of BNIand BCA, because each customer provided high ratings on all indicators of the banks CRM strategy in whichthey saved money. Trust was the most decisive for customers in a comprehensive evaluation of the closeness ofthe relationship with the bank. Furthermore, customers of both banks showed high behavioral loyalty to eachbank.